The Institution of the Right to State Self-defence in the State Security System - Kamiński Mirosław; Stelmach Tomasz (2024)
The aim of the study was to provide an answer as to whether, on the basis of the provisions of the Charter of the UN, the states associated with the UN have sufficient legal provisions to conduct self-defence in the event of an armed attack directed by another state or multiple states.